Hinduism : a cultural perspective - Kinsley, David R. (1993)
"The reference provides an overview of the Hindu religious tradition and describes the essence of the Hindu vision of reality. Provides a historical and analytical discussion of Hindu mythology, art, rituals, and social structure; gives extended portraits of important Hindu thinkers and saints; offers a fuller picture of the role of women in the Hindu religious tradition; shows how the concepts of Dharama and Moksha conflict with one another and how the Hindu tradition insists upon both concepts as essential in fulfilling human destiny. A valuable reference for courses in Asian Religion, Theology, and Asian Philosophy"--from Amazon.com.
Foreword -- Preface -- Part I. An overview of the Hindu tradition: Introduction: Varanasi -- History -- Dissent within the Hindu Religious Tradition -- Hinduism and the arts -- Part II. An analysis of the Hindu tradition: Central Hindu beliefs -- Worship in the Hindu tradition -- Sacred female imagery and women's religious experience in Hinduism -- Hindu social structure -- Symbols and structures: a concluding analysis -- Glossary -- Bibliography -- Index.
Includes bibliographical references (pages 190-193) and index.
Keywords: Hinduism; Hinduism and culture; Hinduism -- Essence, genius, nature